Risk factors for subsequent work disability in patients with acute myocardial infarction. (14th January 2019) - Wang, Mo; Vaez, Marjan; Dorner, Thomas Ernst; Rahman, Syed; Helgesson, Magnus; Ivert, Torbjörn; Mittendorfer-Rutz, Ellenor
Abstract: Background: Scientific knowledge on risk factors for work disability in terms of long-term sickness absence (SA) and disability pension (DP) following acute myocardial infarction (AMI) is limited. The study aimed to investigate socio-demographic, work-related and medical characteristics as risk factors for long-term SA (>90 days) and DP in patients with a first AMI. Methods: This is a population-based cohort study of 8199 individuals aged 19–60 years who had a first AMI during 2008–10 and were alive 30 days after AMI. Univariate and multivariable hazard ratios (HRs) and 95% confidence intervals (CIs) with regard to long-term SA and DP with a 3-year follow-up were estimated by Cox regression. Results: We found a higher risk of long-term SA and DP after AMI in women, those with lower education and previous SA (range of HRs: 1.29–7.34). Older age and being born in non-European countries were associated with a 2- to 3-fold higher risk of DP. Moreover, ST-elevation myocardial infarction (STEMI), musculoskeletal and common mental disorders (CMDs) were risk factors for long-term SA and DP, while diabetes mellitus and stroke were associated with a higher risk of DP (range of HRs: 1.12–2.98). Coronary artery bypass grafting (CABG) compared with percutaneous coronary intervention was associated with a 2-fold higher risk of work disability. Conclusions: Older women, those with lower education and non-European immigrants had a higher risk of work disability after AMI, particularly permanent work disability. STEMI, CABG, diabetes mellitus, stroke, musculoskeletal disorders and CMDs provide important clinical information for work disability after AMI.